2022
DOI: 10.3390/jcm11206121
|View full text |Cite
|
Sign up to set email alerts
|

Association between Renal Function at Admission and COVID-19 in-Hospital Mortality in Southern Italy: Findings from the Prospective Multicenter Italian COVOCA Study

Abstract: Background. Evidence has shown a close association between COVID-19 infection and renal complications in both individuals with previously normal renal function and those with chronic kidney disease (CKD). Methods. The aim of this study is to evaluate the in-hospital mortality of SARS-CoV-2 patients according to their clinical history of CKD or estimated glomerular filtration rate (eGFR). This is a prospective multicenter observational cohort study which involved adult patients (≥18 years old) who tested positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Similarly, to what was recently reported for kidney failure[ 32 ], COVID-19-related mortality risk was strongly associated with the stage of liver impairment. Overall, the 30-d mortality risk is significantly increased in patients with decompensated liver cirrhosis hospitalized for COVID-19[ 15 , 30 ].…”
Section: Liver Cirrhosis and Covid-19 Clinical Outcomessupporting
confidence: 82%
“…Similarly, to what was recently reported for kidney failure[ 32 ], COVID-19-related mortality risk was strongly associated with the stage of liver impairment. Overall, the 30-d mortality risk is significantly increased in patients with decompensated liver cirrhosis hospitalized for COVID-19[ 15 , 30 ].…”
Section: Liver Cirrhosis and Covid-19 Clinical Outcomessupporting
confidence: 82%
“…Recent investigations have revealed that individuals with DKD are more at risk of dying after catching COVID-19 ( 5 ). According to the prospective multicenter Italian COVOCA study, DM and CKD were closely related to intensive care admission and poor prognosis in patients hospitalized for COVID-19 ( 6 ). Thus, to avoid the progression of DKD, early intervention is required.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical variables + FIB-4 Values; 2. Clinical variables + FIB-4 groups [ 23 ]; 3. Clinical variables + Platelets; 4.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical variables + Platelets +AST+ALT; 2) all these models were than compared with the concordance index (C-index) and the multivariable model with the highest score was preferred. The multivariable Cox’s regression models presented general results similar to the previous work, but some of them showed a significant association between mortality risk and FIB-4 Values (Model 1: HR 1.25, 95%CI 1.11–1.41; p<0.001), and the mortality risk is strongly associated with FIB-4 group of advanced fibrosis (Model 2: group 3 vs group 1 -ref-, HR 2.12, 95%CI 1.38–3.28, p<0.001) [ 23 ]. Instead, the other models did not show a significant association between mortality risk and FIB-4 exposure variables ( S1 File ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation